Prevalence of overweight and obesity among undergraduate nursing students: thematic analysis on experiences of overweight and obese participants - Manivannan, Shyamala D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Overweight and obesity is the growing concern of public health. Obesity is on the rise in adults as well as adolescents. Obesity becomes worse with the transition from the teen years into the young adult years. This study aimed to find the prevalence of overweight and obesity in undergraduate nursing students and conduct thematic analysis of the experiences of participants who were overweight and obese. Methods: Descriptive survey and qualitative approach was used to collect data. Self-reported information on weight and height elicited using descriptive survey to assess the prevalence of overweight and obesity. After obtaining informed consent focus group interviews conducted for overweight and obese participants. Interviews transcribed. Results: SPSS version 17 used for analysis. The mean body mass index (BMI) of the participants was 21.46±SD 4.17. The overweight and obesity prevalence was 11.60% and 5.20% respectively. Thematic analysis yielded several themes like change of place, caring family, support and assurance, shyness and bullying, unpleasant experiences and isolation, hereditary etc. Conclusions: Harmful weight reduction strategies to be prevented through good monitoring, mentoring and by establishing “peer support groups” in nursing colleges.